Challenges and innovative solutions at the new construction of the Bözberg Tunnel: Herausforderungen und innovative Lösungen beim Neubau des Bözbergtunnels. Issue 1 (15th February 2018) - Zieger, Thomas; Bühler, Martin; Rick, Beat; Schmid, Werner; Grossauer, Karl
Abstract: In order to further increase the transfer of transalpine traffic through Switzerland from road to rail, the Gotthard axis is to be improved to a 4 m corridor. For this purpose altogether 270 km of railway line between Basel and the Italian border is to be improved to a corner height of 4 m by 2020. The largest individual structure is the new Bözberg Tunnel in the canton Aargau. Various options were investigated for the preliminary design. The best variant turned out to be the new construction of a two‐track tunnel parallel to the existing tunnel. The existing two‐track Bözberg Tunnel, which is not suitable for upgrading to the 4 m standard, will be used as a service and escape tunnel. Various emergency exits lead through five cross passages from the new to the old tunnel. The short construction time of five years until opening on the one hand, and the challenging geology in the Faltenjura with swelling rock mass on the other pose great problems for client, designers, and the contractor. This article reports on these challenges and describes how they have also led to innovative solutions.